Forest cover and agricultural technology - Angelsen, A.; Kaimowitz, D. (Kluwer Academic Publishers, 2001)
A widespread belief among development and forest researchers and practitioners holds that technological progress in tropical agriculture is good for forest conservation. Higher yield enables farmers to produce the same amount of food on less agricultural land. The alternative view suggests that productivity improvements make it more profitable for farmers and companies to convert forests to agriculture. New agricultural technologies should therefore stimulate deforestation. This article synthesizes research done by the Center for International Forestry Research (CIFOR) on this issue. It points to several critical factors which can make new technologies speed up or slow down the rate of deforestation: the market characteristics, the farmers' objectives and constraints, the technologies' labor and capital intensities, and the agricultural systems and areas in which the technology is applied. Several empirical studies are used to illustrate the importance of these factors. While new technologies in frontier agriculture often stimulate forest clearing, conditions and technologies for "win-win" outcomes also exist or can be created by appropriate policies.